2013
DOI: 10.1055/s-0032-1328091
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Anticancer Effects of the Essential Oil from Leaves of Xylopia laevigata

Abstract: Xylopia laevigata, popularly known as "meiú" and "pindaíba", is a medicinal plant used in the folk medicine of the Brazilian Northeast for several purposes. The chemical constituents of the essential oil from leaves of X. laevigata, collected from wild plants growing at three different sites of the remaining Atlantic forest in Sergipe State (Brazilian Northeast), were analyzed by GC/FID and GC/MS. The effect of the essential oil samples was assessed on tumor cells in culture, as well on tumor growth in vivo. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…Among this diversity, several species belonging to the family Annonaceae are noted for their medicinal importance, highlighting species from Annona and Xylopia genera (Di Stasi & Hiruma-Lima 2002). Recent biological investigations regarding essential oils obtained from the species of this family revealed interesting properties, such as antitumour, antioxidant, larvicidal, trypanocidal, antimicrobial and antileishmanial activities (Costa et al 2009(Costa et al , 2011(Costa et al , 2013Quintans et al 2013). Although many of them have been explored from the phytochemical point of view, there are genera with little or no study within the Annonaceae family, such as the genus Bocageopsis, where only the Bocageopsis multiflora has been chemically explored, being the essential oils from its leaves characterised and evaluated against Leishmania amazonensis promastigote forms (Oliveira et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among this diversity, several species belonging to the family Annonaceae are noted for their medicinal importance, highlighting species from Annona and Xylopia genera (Di Stasi & Hiruma-Lima 2002). Recent biological investigations regarding essential oils obtained from the species of this family revealed interesting properties, such as antitumour, antioxidant, larvicidal, trypanocidal, antimicrobial and antileishmanial activities (Costa et al 2009(Costa et al , 2011(Costa et al , 2013Quintans et al 2013). Although many of them have been explored from the phytochemical point of view, there are genera with little or no study within the Annonaceae family, such as the genus Bocageopsis, where only the Bocageopsis multiflora has been chemically explored, being the essential oils from its leaves characterised and evaluated against Leishmania amazonensis promastigote forms (Oliveira et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several species are employed in popular medicine with a remarkable set of purposes [2,3]. Previous phytochemical investigations report this genus as source of biologically active diterpenes [4,5].…”
Section: Previous Studiesmentioning
confidence: 99%
“…Marya et al [26] did not observe a hemolytic effect at a concentration of 0.01% in the samples when evaluating the hemolytic activity of essential oil of Quintans et al [27] evaluated the effect of essential oil from Xylopia laevigata on rat erythrocytes (2% hematocrit) and observed hemolysis at concentrations ranging from 31.25 to 500 μg•mL −1…”
Section: Hemolytic Activitiesmentioning
confidence: 99%
“…The results observed by these authors differ from those obtained in this work for the Mentha essential oils, which presented a high hemolytic activity even when evaluated at low concentrations. Quintans et al [27] identified γ-muruleno, δ-cadineno, germacrene-B, α-co-paene, bicyclogermacrene and E-caryophyllene (all sesquiterpenes) as the principal constituents. The essential oils from Mentha species contained oxygenated sesquiterpenes as the principal constituents, differentiating the compositions of the oils and, consequently, the activities.…”
Section: Hemolytic Activitiesmentioning
confidence: 99%